The Impact of Financial Literacy, Financial Inclusion, and Income on Financial Behavior of Msmes in The Culinary Sector in Sekadau Regency - Utari, Ria; Suryadi, Edy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to examine the impact of financial literacy, financial inclusion, and income on the financial behavior of MSMEs in the culinary sector in Sekadau Regency. MSMEs play a significant role in the economy, yet many struggle with financial management. The research uses an associative method to understand the relationship between these variables and the financial behavior of MSMEs. Data was collected through questionnaires distributed to 150 MSME owners in the culinary sector in Sekadau, with additional secondary data obtained from official documents. The results show that financial literacy, financial inclusion, and income all have a positive and significant impact on the financial behavior of MSMEs. Among these variables, income has the largest impact, followed by financial inclusion and financial literacy. The F-test results indicate that, collectively, these three variables have a significant effect on financial behavior. The t-test results also show that financial literacy and financial inclusion have a positive effect on financial behavior individually, with income having the greatest impact. Additionally, the normality test results indicate that the data is normally distributed, the linearity test shows a linear relationship between the variables, and the multicollinearity test confirms that there is no high correlation between the independent variables. Overall, the study suggests that improving financial literacy, increasing access to financial services, and boosting income can help MSMEs improve their financial behavior. These findings provide valuable insights for policymakers and financial institutions in designing programs that can enhance financial management among MSMEs.